Transoral laser microsurgery for the treatment of oropharyngeal cancer: the Dalhousie University experience. Issue 1 (December 2015) - Melong, J.C.; Rigby, M.; Bullock, M.; Hart, R.; Trites, J.; Taylor, S.
Abstract Objective The optimal treatment strategy for oropharyngeal squamous cell carcinoma is highly debated. However, growing evidence supports the use of minimally invasive techniques, such as transoral laser microsurgery (TLM), as a first-line treatment modality for these carcinomas. The purpose of our study was to assess the efficacy and safety of TLM for the treatment of primary and recurrent oropharyngeal carcinomas. Methods All patients with oropharyngeal carcinoma undergoing TLM at the QEII Health Sciences Centre in Halifax, Nova Scotia were identified within a prospective database monitoring TLM outcomes. Kaplan-Meier survival analysis was used to evaluate the following end points at 36 months: local control (LC), disease-specific survival (DSS), and disease-free survival (DFS). Safety endpoints included complications following surgery and long term morbidity related to TLM. Results Between 2003 and 2014, 39 patients with oropharyngeal carcinoma underwent TLM resection. Twenty-eight (72 %) patients had primary carcinoma, nine (23 %) were radiation/chemoradiation (RT/CRT) failures, and two (5 %) had second primaries following previous RT/CRT. Three patients had stage I disease, 8 stage II, 5 stage III, and 23 stage IV disease. HPV status was available for 26 patients, of which 23 (88 %) had HPV positive disease. Kaplan-Meier estimates of 36-month LC, DSS, and DFS for primary oropharyngeal carcinomas were 85.5 % (SE 10.6 %), 85.7 % (SE 13.2 %) and 77.7 % (SE 12.5 %) respectively. Thirty-six-month outcomes for RT/CRT failures were 66.76 % (SE 15.7 %) for LC and 55.6 % (SE 16.6 %) for DSS and DFS. Three patients developed complications following surgery. Conclusions Observed 36-month efficacy and safety outcomes support the use of TLM for the treatment of primary and recurrent oropharyngeal carcinoma.